2021
DOI: 10.3390/molecules26133837
|View full text |Cite
|
Sign up to set email alerts
|

UiO-66-NH2 and Zeolite-Templated Carbon Composites for the Degradation and Adsorption of Nerve Agents

Abstract: Composites of metal-organic frameworks and carbon materials have been suggested to be effective materials for the decomposition of chemical warfare agents. In this study, we synthesized UiO-66-NH2/zeolite-templated carbon (ZTC) composites for the adsorption and decomposition of the nerve agents sarin and soman. UiO-66-NH2/ZTC composites with good dispersion were prepared via a solvothermal method. Characterization studies showed that the composites had higher specific surface areas than pristine UiO-66-NH2, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…47,48 This material's application in CO 2 capture requires gas sorption measurements to verify the porosity of synthesized materials. 49,50 The S BET of the material synthesized in this work is comparable to other rapid syntheses, as Huelsenbeck et al 31 reported rapid aqueous syntheses of UiO-66 and UiO-66-NH 2 , which presented S BET of 339 and 717 m 2 g −1 , respectively, owing to defects that can form as a result of fast crystallization. In this work, gas sorption measurements revealed an S BET of 691 m 2 g −1 , a pore volume of 0.65 cm 3 g −1 , and a pore diameter of 3.7 nm.…”
Section: ■ Materials and Methodssupporting
confidence: 72%
See 1 more Smart Citation
“…47,48 This material's application in CO 2 capture requires gas sorption measurements to verify the porosity of synthesized materials. 49,50 The S BET of the material synthesized in this work is comparable to other rapid syntheses, as Huelsenbeck et al 31 reported rapid aqueous syntheses of UiO-66 and UiO-66-NH 2 , which presented S BET of 339 and 717 m 2 g −1 , respectively, owing to defects that can form as a result of fast crystallization. In this work, gas sorption measurements revealed an S BET of 691 m 2 g −1 , a pore volume of 0.65 cm 3 g −1 , and a pore diameter of 3.7 nm.…”
Section: ■ Materials and Methodssupporting
confidence: 72%
“…The product presents a high volume and pore diameters compared to those found in other research. 49,50 Isotherms measured at 288, 298, and 308 K (Figure 2B) were used to find the isosteric enthalpy of adsorption which was calculated via the Clausius−Clapeyron equation, providing a value of ΔH ad = −30 ± 2 kJ mol −1 . This value implies the interaction with CO 2 was physisorption, consistent with reported values for conventionally synthesized UiO-66-NH 2 .…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The aforementioned analysis shows that PTSA in acidic DES and ZrOCl 2 preliminarily forms Zr(IV) oxo organic acid framework. With the addition of mixed H 2 BDC linker and basic DES, the strong hydrogen bond effect between PTSA and MIm can accelerate the exchange of H 2 BDC and PTSA in Zr(IV) oxo organic acid framework [ 51 ]. This process has also been demonstrated by the acceleration of CH 3 COOH and HCOOH in ionic liquid for the formation of metal organic framework [ 27 , 50 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
“… 27 With the development of technology and the increasing application of MOFs, their synthesis methods have become increasingly diversified. The existing synthetic methods include the hydrothermal method, 31 solvothermal method, 32 , 33 ionothermal synthesis, 34 , 35 ultrasonicated method, 36 spray drying synthesis, 37 , 38 and microwave-assisted hydrothermal synthesis. 39 , 40 Different synthesis techniques have various benefits and drawbacks.…”
Section: Synthesis Of Metal-organic Frameworkmentioning
confidence: 99%